O processo de ensino-aprendizagem do conceito de energia na termoquímica e a relação com o cotidiano de alunos do ensino médio - Marques, Ataiany dos Santos Veloso (2012)
This work dealt with the topic of teaching the concept of energy in thermochemistry. For that was built the following objectives: overall goal - Analyze how we approached the scientific concept of energy in Thermochemistry and its relationship with every day in the process of teaching and learning with students of 2nd year of high school; specific objectives: Identify prior knowledge of students regarding scientific concept of energy in thermochemical related to daily life, identify which design teacher about teaching the scientific concept of energy in thermochemical related to everyday life, describe the methodology used by the teacher in the teaching-learning concept energy, identify the relationship established the scientific concept of energy in thermochemical with everyday according to the speech of students. We like the theory and Marxist perspective vigostkiana. How Methodology Data collection was performed on a questionnaire prior knowledge about the concept of energy, individual interviews with the teacher, focus groups with students and participant observation in the classroom. For data analysis we used the method of content analysis. The following results were raised to working with chemistry professor dogmatic, students fail to make a clear link between the taught in the room with your daily life, like getting different worlds that no connections between the perceived and personal context of each. In observation was noticed that the adopted methodology is proposed as content-based. We believe students potentially open to be worked needing only a new way of teaching that provides it.